A reversible rhodamine 6G-based fluorescence turn-on probe for Fe3+ in water and its application in living cell imaging. Issue 113 (24th November 2016) - Liu, Yaming; Shen, Rong; Ru, Jiaxi; Yao, Xiang; Yang, Yang; Liu, Haile; Tang, Xiaoliang; Bai, Decheng; Zhang, Guolin; Liu, Weisheng
Abstract : A reversible fluorescent probe L based on rhodamine 6G was synthesized for the optical detection of Fe 3+ in water. Abstract : A reversible fluorescent probe L based on rhodamine 6G is synthesized for the optical detection of Fe 3+ in water. This probe displays favorable selectivity for Fe 3+ with a 1 : 1 stoichiometry. It displays a fluorescence turn-on response in the process of rhodamine ring opening with Fe 3+ and a fluorescence turn-off response with the addition of Na4 P2 O7 to the L-Fe 3+ complex. The association constant between the probe and Fe 3+ was detected to be 3.5 × 10 4 M −1, and the corresponding detection limit was calculated to be 1.9 × 10 −8 M according to fluorescence titration analysis. Furthermore, bioimaging investigations indicated that this probe was cell permeable and suitable for monitoring intracellular Fe 3+ in living cells by confocal microscopy.